Study of plasma immersion ion implantation into silicon substrate using magnetic mirror geometry - Pillaca, E. J. D. M.; Ueda, M.; Kostov, K. G. [UNESP]; Reuther, H. (Elsevier B.V., 2012)
The effect of magnetic field enhanced plasma immersion ion implantation (PIII) in silicon substrate has been investigated at low and high pulsed bias voltages. The magnetic field in magnetic bottle configuration was generated by two magnetic coils installed outside the vacuum chamber. The presence of both, electric and magnetic field in PIII creates a system of crossed E x B fields, promoting plasma rotation around the target. The magnetized electrons drifting in crossed E x B fields provide electron-neutral collision. Consequently, the efficient background gas ionization augments the plasma density around the target where a magnetic confinement is achieved. As a result, the ion current density increases, promoting changes in the samples surface properties, especially in the surface roughness and wettability and also an increase of implantation dose and depth. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Plasma immersion ion implantation with magnetic field; Silicon; Magnetic mirror geometry; Crossed E x B fields